Religion and Globalization in Laos - Boike Rehbein (Journal of Current Southeast Asian Affairs, 2009)
According to Eurocentric sociology, modernization is supposed to make religion secular, a functional system, or a private matter. A closer analysis of the impact of contemporary globalization on religion in Laos shows that these tendencies can only be observed in certain social groups and in certain realms of religion. Some social groups preserve or reinvent religious traditions, others construct a new identity, and some do tend towards secularism or differentiation. The paper investigates these tendencies, referring to an empirical case study. It proposes to explain them within a conceptual framework adapted to societies of the global South which focuses on the concepts of social structure, division of work, socioculture, and institution. On the basis of these concepts, the paper proposes to distinguish between different religious realms, namely, belief, performance, and knowledge. In each of these three realms, different tendencies and social distributions can be observed.